Digital Transformation and Internationalization of SMEs: Emerging Challenges, Opportunities and Threats - Veglio, Valerio; Nippa, Micheal; Gunkel, Marjaana (Piccola Impresa / Small Business, 2020)
Understanding the influence of the digitalization on the internationalization of SMEs are becoming a fundamental issue for both scholars and decision makers. This special issue includes empirical and conceptual articles that seek to analyze how the digital transformation is changing the internationalization approach of SMEs. Particular attention is paid on emerging challenges, opportunities and threats. The selected contributions draw on different frameworks and methodological approaches as the authors have expertise in different disciplines (i.e. international business, international entrepreneurship, and family business). In details, the papers provide new insights in the field of international business with a focus on the following specific topics: digital internationalizing firms, international new ventures and new digital technologies, Industry 4.0 investments and internationalization, and board interlocks and international joint ventures.